Revealing the excited-state mechanisms of the polymorphs of a hot exciton material - Ziqi Deng; Chao Huang; Yunfeng Luo; Jiaxing He; Lan Li; Xinyu Pang; Guanheng Huang; David Lee Phillips (Nature Communications)
Abstract As the investigation of high efficiency thermally activated delayed fluorescence (TADF) materials become more mature, regulating the emission properties for single organic luminescence molecules has gained increasing interest recently. Herein, the donor-acceptor compounds F-AQ comprised of fluorene and anthraquinone is reported, and it exhibits a polymorphism with muti-color emission and TADF from high-level intersystem crossing (hRISC). The photodynamics and excited-state transient species were studied by femtosecond transient absorption (fs-TA) spectroscopy. As a result, an unambiguous signal of through space charge transfer (TSCT) was observed in the fs-TA spectra of the crystal with the π-π interaction between the fluorene and anthraquinone groups, whereas the other amorphous solids and crystal only show a conventional deactivation pathway of hRISC-TADF. In this study, we successfully realize the direct observation of the morphism-dependent TSCT in a crystal, which provides the observations in solid-state ultrafast excited-state dynamics and deepens the insight into the design of potential mechanochromic materials and thermochromic utilization of the polymorphism of organic luminescence molecules.